PERANCANGAN KEAMANAN CCTV DENGAN MENGGUNAKAN RASPBERRY PI MODEL B DAN SENSOR OBJECT PIR - Zakial Vikki; Rudi Hendrawan (LPPM-UNIKI, 2020)
Based on the idea of making a space security design system, this research will make a prototype of a space accesssecurity system using a PIR object sensor. In the study of space access security systems using one of the developing microcontrollers, the Raspberry Pi. Raspberry Pi is a microcontroller based on SBC (Board Chip system). Raspberry Pi or often abbreviated as Raspi, is a single board computer (Single Board Circuit / SBC) which is as large as a credit card.You could say Raspi is a PC (Personal Computer) because its function can replace desktop computers today and its small size so it is practically carried anywhere. The purpose of this study is to produce a security system that is cost-effective and security is also guaranteed through CCTV using Raspberry Pi and the Object Pir Sensor. This security system is expected to be able to improve the security of space access in our environment, both at home and on campus. Key words: CCTV security design using Raspberry Pi and PIR Object Sensor